2015
DOI: 10.1021/acs.jpca.5b06053
|View full text |Cite
|
Sign up to set email alerts
|

Valence and Ionic Lowest-Lying Electronic States of Isobutyl Formate Studied by High-Resolution Vacuum Ultraviolet Photoabsorption, Photoelectron Spectroscopy, and Ab Initio Calculations

Abstract: The highest resolution vacuum ultraviolet photoabsorption spectrum of isobutyl formate, C5H10O2, yet reported is presented over the energy range 4.5-10.7 eV (275.5-118.0 nm) revealing several new spectral features. Valence and Rydberg transitions and their associated vibronic series observed in the photoabsorption spectrum have been assigned in accordance with new ab initio calculations of the vertical excitation energies and oscillator strengths. Calculations have also been carried out to determine the ioniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
5
7
0
Order By: Relevance
“…The first band, shown in Figure 2, with a maximum cross section of 0.19 Mb, has been identified as the transition from the terminal oxygen in-plane lone pair (n O1 ) to the first π antibonding molecular orbital (π*(C=O) ← n O1 19a )(1 1 A ← 1 1 A ). The calculated value of the oscillator strength, 1 × 10 −3 , is comparable with the values obtained for the previously analysed esters [11][12][13]. The position of the maximum cross section of this band also agrees well with the value given by others, obtained from the spectrum of the liquid sample, i.e.…”
Section: Valence States and Transitions Of Ethyl Acetatesupporting
confidence: 90%
See 2 more Smart Citations
“…The first band, shown in Figure 2, with a maximum cross section of 0.19 Mb, has been identified as the transition from the terminal oxygen in-plane lone pair (n O1 ) to the first π antibonding molecular orbital (π*(C=O) ← n O1 19a )(1 1 A ← 1 1 A ). The calculated value of the oscillator strength, 1 × 10 −3 , is comparable with the values obtained for the previously analysed esters [11][12][13]. The position of the maximum cross section of this band also agrees well with the value given by others, obtained from the spectrum of the liquid sample, i.e.…”
Section: Valence States and Transitions Of Ethyl Acetatesupporting
confidence: 90%
“…1). In our previous studies on the related compounds of ethyl formate [12] and isobutyl formate [13] it was shown that a proper assignment of the spectroscopic features is obtained using calculations on a single conformer. Therefore, in the present study theoretical computations are only performed on the trans-trans conformer.…”
Section: Structure Of Ethyl Acetatementioning
confidence: 99%
See 1 more Smart Citation
“…The apparatus was described previously in detail [25] and a specific description of the operation in the threshold mode was also provided [26]. Although it was primarily designed to be used for measurements of noble gases and small, diatomic molecules, it was recently proven that it may also be used for measurements on more complicated systems, such as pyrimidine and of its heavier derivatives [27] or esters [28,29].…”
Section: Threshold and Photoelectron Spectramentioning
confidence: 99%
“…The only previous studies of this molecule concern its first ionization energy [1]. The absolute photoabsorption cross sections of isobutyl acetate presented here are needed for modeling studies of the Earth's atmosphere and radiation-induced chemistry of esters, and together with the results on previously analysed members of this class: methyl formate [2], ethyl formate [3], isobutyl formate [4] and ethyl acetate [5], help to understand the chemistry of esters and their electronic state spectroscopies.…”
Section: Introductionmentioning
confidence: 96%